MANAJEMEN PENDIDIKAN KEWIRAUSAHAAN SEKOLAH MENENGAH KEJURUAN DALAM MEMBENTUK KEMANDIRIAN SISWA (STUDI PADA SEKOLAH MENENGAH KEJURUAN TRISAKTI JAYA BANDARLAMPUNG) - Dewi, Rita; Noviarita, Heni; Amirudin, Amirudin (STIT AL MULTAZAM, 2023)
This qualitative research aims to describe the planning, implementation, and evaluation of entrepreneurship education management in shaping the independence of students SMK Trisakti Jaya Bandarlampung. Independent is the attitude of someone who can do things on their own without relying on others. Independence will make a person able to make his own decisions with confidence and responsibility for his decisions. As a form of attitude, independence can be formed by internalization. The results of the research that the formation of student independence with entrepreneurial character at SMK Trisakti Jaya Bandarlampung teaches core values that need to be transformed in education, namely honesty and discipline. Such transformed values in order to shape, maintain, build and develop, even in certain efforts lead to changing the culture of society. The learning of the values of independence associated with entrepreneurship is sought to be integrated into each subject. The role of the teacher of entrepreneurship subjects determines the formation of student independence because it takes real action in the form of creativity to foster entrepreneurial interest in schools so that independence is embedded. Careful planning of learning materials, must adopt more entrepreneurial values and implement in the form of curricular ectra that adapts to the major and its competence. Industrial work practices or PKL that contribute to student independence need to be well managed and managed, as well as industrial visits or study tours because they can provide benefits in forming independence. The success rate in terms of planning has been good, as well as its implementation, but the evaluation to find out the factors that support and hinder the management of entrepreneurship education in shaping student independence has not been realized properly.